Cloning and Expression of N-CFTX-1 Antigen from Chironex fleckeri in Escherichia coli and Determination of Immunogenicity in Mice - Hossein JAFARI; Saeid TAMADONI JAHROMI; Jamil ZARGAN; Ehsan ZAMANI; Reza RANJBAR; Hossein HONARI (Tehran University of Medical Sciences, 2021)
Background: Most jellyfish species are poisonous. Human victims of jellyfish sting each year are 120 million. Chironex fleckeri is a venomous box jellyfish that inflicts painful and potentially fatal stings to humans. The CfTX-1 is one of the antigenic proteins of venom that is suggested to stimulate the immune system for treatment and vaccine. This study aimed to clone and express the CfTX-1 antigen in E. coli and then to determine the synthesis of related antibody in the mice. Methods: The study was performed in the Persian Gulf and Oman Sea Ecology Research Center, Bandar Abbas, Iran in autumn 2016. The synthetic CfTX-1 gene in PUC57 plasmid was purchased from Nedaye Fan Company. The 723 bp fragment of N-CfTX-1 was amplified by PCR, PUC57 plasmid containing CfTX-1 with BamHI SalI restriction enzyme sites were subcloned in pET28a [+] expression vector and transformed into E. coli BL21 (DE3). The CfTX-1 gene expression was induced by IPTG. Then antibody produced from the mice serum were isolated and confirmed by ELISA. After protein purification, resulted antigen was injected to mice in 4 repeats and then evaluated the rate of antibody in mice serum. Mice were challenged by the Carybdea alata. Results: The 726 bp of N-CfTX-1 were cloned in a vector of expression pET28a [+] and confirmed by PCR, sequencing and enzymatic analysis. Moreover, the recombinant protein was confirmed by SDS-PAGE and Western blotting. Then the antibody was isolated from mice serum and confirmed by ELISA test. The results showed that immunized mice tolerated 50x LD50[1] of jellyfish venom. Conclusion: The CfTX-1 recombinant protein was able to protect the BALB/c mice against jellyfish venom. The produced protein can be used as a candidate for vaccine against jellyfish venom.